MiRNA regulation of innate immunity. Issue 6 (14th April 2018) - Momen‐Heravi, Fatemeh; Bala, Shashi
Abstract: MicroRNAs (miRNAs) are small noncoding RNA and are pivotal posttranscriptional regulators of both innate and adaptive immunity. They act by regulating the expression of multiple immune genes, thus, are the important elements to the complex immune regulatory network. Deregulated expression of specific miRNAs can lead to potential autoimmunity, immune tolerance, hyper‐inflammatory phenotype, and cancer initiation and progression. In this review, we discuss the contributory pathways and mechanisms by which several miRNAs influence the development of innate immunity and fine‐tune immune response. Moreover, we discuss the consequence of deregulated miRNAs and their pathogenic implications. Abstract : Review on role miRNAs in innate immunity as well as mechanistic pathways regulated by key miRNAs.